Dexamethasone Use in the Treatment of Pediatric Deep Neck Space Infections. (April 2020) - Tansey, James B.; Hamblin, John; Mamidala, Madhu; Thompson, Jerome; Mclevy, Jennifer; Wood, Joshua; Sheyn, Anthony
Objectives: Assess the outcome of Intravenous (IV) dexamethasone in the treatment of pediatric deep neck space infections (DNSI) in combination with IV antibiotics. Methods: Retrospective chart review of pediatric patients admitted for a DNSI from March 2014 to June 2016. Patient characteristics including demographics, abscess type, antibiotic, dexamethasone, surgery, culture, and length of stay (LOS) were obtained. Patients treated with antibiotics alone versus antibiotics and dexamethasone were compared. Primary outcome measures were rate of surgical drainage and LOS. Results: Overall 153 patients with DNSI were identified, including 62 lateral neck, 18 parapharyngeal, 40 peritonsillar, 32 retropharyngeal, and 1 submandibular. All patients received antibiotics. Dexamethasone was used in 35% of patients. The rate of surgical drainage in the dexamethasone and non-dexamethasone group was 36% and 53% respectively ( P = .043). LOS was shorter for the dexamethasone group (2.9 days) compared to the non-dexamethasone group (3.8 days) but was non-significant, P -value-.09. The most common microorganisms cultured were MRSA (25), MSSA (11), and Streptococcus pyogenes (10). Conclusion: Dexamethasone use was associated with a decreased rate of surgical drainage in pediatric patients with DNSI. Further prospective study is needed to determine the role of dexamethasone in treatment.